2020
DOI: 10.1093/ajhp/zxaa133
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy leadership during emergency preparedness: Insights from the Middle East and South Asia

Abstract: The Frontline Pharmacist column gives staff pharmacists an opportunity to share their experiences and pertinent lessons related to day-to-day practice. Topics include workplace innovations, cooperating with peers, communicating with other professionals, dealing with management, handling technical issues related to pharmacy practice, and supervising technicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…According to a recently published report addressing pharmacy leadership preparedness during emergency in the Middle East and South Africa, many clinical activities of pharmacists have continued and been performed through virtual tools and phone calls to maintain physical distancing, including medication reconciliation, bed-side discharge counseling, clinical rounds, anticoagulation, and heart failure clinics. 7 …”
Section: Introductionmentioning
confidence: 99%
“…According to a recently published report addressing pharmacy leadership preparedness during emergency in the Middle East and South Africa, many clinical activities of pharmacists have continued and been performed through virtual tools and phone calls to maintain physical distancing, including medication reconciliation, bed-side discharge counseling, clinical rounds, anticoagulation, and heart failure clinics. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Although pharmacists have been shown to share the most up-to-date evidence-based information from international sources such as the World Health Organization (WHO), the US Pharmacists Association, and the US Occupational Safety and Health Administration, and prevent crucial medication misuse or accidental loss. [20][21][22][23][24][25] Indeed, pharmacists have increased their knowledge of drugs and their side effects. At the same time, society chose pharmacists as the first direct source of up-to-date, trustworthy, and unbiased information.…”
Section: Conclusion/discussionmentioning
confidence: 99%
“…Personal fears regarding contamination risk originating in nursing homes or between colleagues was an issue in some HPs and should be considered in any future pandemic preparedness plans. Regarding psychological support for their teams, pharmacy heads should listen to staff's concerns and take proactive steps to identify and offer help and guidance to those at risk of burnout or experiencing psychological distress (16). To this end, 40% of HPs introduced team briefings and debriefings, and hierarchies calmed and reassured their staff.…”
Section: Discussionmentioning
confidence: 99%
“…In some countries (14), HPs reorganised their activities to limit their HR risks: roles were redistributed and non-pharmacist staff were used to assist in manufacturing units and answer the phone (15). Another study reported HPs encouraging work from home and physical distancing (16). Our survey found that 47% (n=20) of HPs moved at-risk employees to safer environments.…”
Section: Discussionmentioning
confidence: 99%